Analysis of the soil and microclimate relationship in two dolines of Carso Huasteco, Mexico - Quintero-Ruiz, Joab R.; Yáñez-Espinosa, Laura; Flores, Joel; Fortanelli, Javier; De-Nova, Arturo; Reyes-Hernandez, Humberto; Rodas-Ortíz, Juan P. (JNRD - Journal of Natural Resources and Development, 2019)
Dolines are karst depressions whose environmental and climatic characteristics in tropical regions are not well known. By measuring and analyzing different components of the microclimate in two dolines located in Tamasopo, Mexico, we aim to contribute to the understanding of the climatic conditions in these formations. The variables analyzed include temperature, solar radiation, soil and air humidity, as well as their relationship to physical and chemical characteristics of the soil such as pH, conductivity, texture, and the content of organic matter, carbon, nitrogen, phosphorus, calcium, potassium, sodium and magnesium. Measurements and soil samples were taken in three strata: bottom, slope and exterior. The results show a gradient in the climatic variables along the three strata, as well as higher concentrations of all elements, except phosphorus, in soil from the dolines, with respect to the exterior. Furthermore, statistical analysis shows a high correlation between the environmental conditions and edaphic properties. The micro climatic factors of the dolines generate a different environment, rich in humidity and with temperatures commonly lower than those present in tropical regions. These conditions cause abrupt changes in the physical and chemical composition of the soil, which present high concentrations of nutrients.
Keywords: Biogeochemistry; Gradient; Karst; Macronutrients